Dogs and pigs are transport hosts of Necator americanus: Molecular evidence for a zoonotic mechanism of human hookworm transmission in Ghana. (11th June 2020) - Boyko, Ryan H.; Marie Harrison, Lisa; Humphries, Debbie; Galvani, Alison P.; Townsend, Jeffrey P.; Otchere, Joseph; Wilson, Michael D.; Cappello, Michael
Abstract: Hookworm infection ( Necator americanus and Ancylostoma spp) causes significant morbidity in resource‐limited countries. Dog and pig ownership is associated with human infection, although the mechanism through which animals increase risk remains unknown. We first confirmed this association in Kintampo North, Ghana, using a retrospective analysis and serology, followed by a prospective molecular study of animal faeces. As a proxy of exposure to dog faeces, we analysed immunoreactivity of human serum to the zoonotic nematode Toxocara canis . Anti‐ Toxocara antibodies were present in 62% of samples ( n  = 89), and reactivity was associated with dog ownership. A subsequent prospective study revealed that 43% of dog and 56% of pig faecal samples contained hookworm eggs by microscopy. PCR analysis confirmed the presence of N. americanus DNA in 47% of samples from dogs and 56% pig samples. Nematode larvae were successfully cultured from samples collected from 36 dogs and seven pigs. These results demonstrate that dogs and pigs have a likely role in the transmission of N. americanus in endemic communities.